Riset Bibiliometrik: AI Generative Content dalam Art and Designs (2020-2024) - Elvina Nanda Meidiani; Kurniawan Saefullah; Kasno Pamungkas (LP2M ISBI Bandung, 2026)
This paper analyzes the development of Artificial Intelligence Generated Content (AIGC) research in art and design from 2020 to 2024 using bibliometric methods. Addressing the limited systematic mapping of this field, it examines publication trends, dominant keywords, major institutions, and research clusters. A total of 341 Scopus-indexed articles were screened using PRISMA guidelines and analyzed with VOSviewer. Results reveal rapid growth after 2021, led by China, the United States, and the United Kingdom. Four main clusters emerged: AI technical foundations, creative applications, human–AI interaction, and computer vision. Hasselt University and the University of Antwerp were among the leading contributors. This study provides a structured overview of AIGC in creative fields and highlights computer-aided design and product design as promising directions for future research.